Ketone Administration for Seizure Disorders: History and Rationale for Ketone Esters and Metabolic Alternatives - Poff, Angela M.; Rho, Jong M.; D’Agostino, Dominic P. (Frontiers in Neuroscience, 2019)
The ketogenic diet (KD) is a high-fat, low-carbohydrate treatment for medically intractable epilepsy. One of the hallmark features of the KD is the production of ketone bodies which have long been believed, but not yet proven, to exert direct anti-seizure effects. The prevailing view has been that ketosis is an epiphenomenon during KD treatment, mostly due to clinical observations that blood ketone levels do not correlate well with seizure control. Nevertheless, there is increasing experimental evidence that ketone bodies alone can exert anti-seizure properties through a multiplicity of mechanisms, including but not limited to: (1) activation of inhibitory adenosine and ATP-sensitive potassium channels; (2) enhancement of mitochondrial function and reduction in oxidative stress; (3) attenuation of excitatory neurotransmission; and (4) enhancement of central γ-aminobutyric acid (GABA) synthesis. Other novel actions more recently reported include inhibition of inflammasome assembly and activation of peripheral immune cells, and epigenetic effects by decreasing the activity of histone deacetylases (HDACs). Collectively, the preclinical evidence to date suggests that ketone administration alone might afford anti-seizure benefits for patients with epilepsy. There are, however, pragmatic challenges in administering ketone bodies in humans, but prior concerns may largely be mitigated through the use of ketone esters or balanced ketone electrolyte formulations that can be given orally and induce elevated and sustained hyperketonemia to achieve therapeutic effects.